PENGARUH KUALITAS PELAYANAN ONLINE CUSTOMER REVIEW DAN PROMOSI MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN MELALUI MINAT BELI SEBAGAI VARIABEL INTERVENING (Studi Pada Pembeli Online Tokopedia di Czyan Store) - Liranti Aranida Hernadi; Lusiana Tulhusnah; Riska Ayu Pramesthi (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of service quality, online customer reviews, and social media promotion on purchase decisions through purchase intention as an intervening variable (A Study on Online Buyers of Czyan Store on Tokopedia). The research employed a quantitative approach using a survey method with questionnaires distributed to 80 respondents. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings indicate that service quality has a significant positive effect on purchase intention. Online customer reviews have a positive but not significant effect on purchase intention. Social media promotion has a significant positive effect on purchase intention. Service quality has a positive but not significant effect on purchase decisions. Online customer reviews also show a positive, albeit non-significant, effect on purchase decisions. Similarly, social media promotion has a positive but not significant effect on purchase decisions. Purchase intention has a significant positive effect on purchase decisions. Furthermore, service quality has a significant positive impact on purchase decisions, influencing purchase intention. Online customer reviews have a positive but non-significant effect on purchase decisions, influencing purchase intention. Social media promotion has a significant positive impact on purchase decisions, influencing purchase intention.